Pengaruh Transparansi Dan Akuntabilitas Terhadap Pengumpulan Dana Zakat, Infaq Dan Shodaqoh Pada Laz Di Surabaya - Dina Fitrisia Septiarini (AKRUAL: JURNAL AKUNTANSI, 2011)
AbstractPotential acceptance of zakat in Indonesia is very large, considering Indonesia is a country with the largest Muslim population in the world. Potential new revenue forecast comes from the charity, not including potential revenues derived from infaq and shodaqoh and endowments. Zakat earnings potential is still far from reality receiving alms, infaq and shodaqoh, acceptance of zakat in Indonesia in 2009 amounted to Rp. 250 billion or just 0.13% of the existing potential of zakat. Zakat also serves as worship that bridges the rich and the poor in order to avoid extreme disparities. In the Qur'an itself there are 27 verses that align with the obligation of zakat obligations prayer. This study uses quantitative methods by taking the population is the Muzakki the zakat funds, infaq and shodaqoh through the Amil Zakat Foundation (LAZ) in Surabaya while the sample used is the Muzakki from 5 LAZ raised in Surabaya by 75 respondents. Using Multiple Regression analysis with SPSS. The results showed that there is a positive correlation or there is the influence of sermons and the mandate of charity fundraising, and shodaqoh infaq on LAZ in Surabaya.